Avaliação dos efeitos do Bisfenol A em queratinócitos e células de neoplasia de cavidade oral - Tatiana Fernandes Araujo Almeida (2020)
Bisphenol A (BPA) is a monomer used to product plastic bottles, food packaging, inner coating of food cans, thermal papers, medical devices, dental resins and various other materials. Due to its chemical structure, this monomer acts as a deregulator of the endocrine system and its effects are associated with cancers in different organs and tissues such as breast, endometrium, ovary, prostate, testis and thyroid. BPA has been detected in several human fluids, including saliva, however its effects on the normal oral mucosa and neoplastic oral cells have not been investigated yet. Thus, the objectives of the present study were 1) to verify the effects of chronic exposure to BPA in salivary glands and oral mucosa in vivo and 2) to evaluate the effects of BPA in vitro on oral tumor cells and keratinocytes. To meet objective 1, male and female mice received BPA (200 mg / mL) in drinking water for 6 weeks. The oral mucosa (palate, tongue and buccal mucosa) and submandibular salivary glands were evaluated microscopically. To meet objective 2, the response to BPA was examined in immortalized cell lines NOK SI (keratinocyte); HN12, HN13 (OSCC), UM HMC1 and UM HMC3a (salivary gland tumor). The following parameters were evaluated: viability, proliferation, invasion, angiogenesis, cytokine and growth factors production. Results. Exposure of mice to BPA resulted in microscopic changes characterized by increased thickness of the oral mucosa epithelium (palate, tongue and buccal mucosa) and a reduction in the number of submandibular salivary glands acini. There was also an accumulation of BPA in the oral tissues. In vitro, in OSCC cells, BPA increased cell proliferation and invasion, vimentin expression, induced secretion of cytokines and growth factors, and induced histone H3 acetylation. In oral keratinocytes, BPA increased cell proliferation and induced secretion of growth factors and estrogen receptor (ER) α and β expression. The effects of BPA were reversed in the presence of the pure ER antagonist. In salivary gland tumor cell lines, BPA did not alter the proliferation and induced the expression of p63. BPA mechanism of action involves its interaction with ER, since the effects were reverted in the presence of pure receptor antagonist. In conclusion, BPA induces morphological changes in oral tissues and molecular changes in keratinocytes and OSCC cells. The mechanisms which BPA induces these changes are dependent to the BPA-ER interaction and histone acetylation